Experiences and expertise in building Arabic electronic dictionaries: an example from the lingual electronic dictionary - Mohd Feham Md Ghalib; Mona Mohammed Abdullah Al-Qartoubi; Malik Hamood Said al-Noumani (Penerbit Universiti Kebangsaan Malaysia, 2022)
It is crucial to develop electronic Arabic dictionaries and transfer them from mere rigid dictionaries to interactive electronic dictionaries rich in everything that technological development has done through well-thought-out and effective approaches. This would not only enrich the Arabic language learner with countless linguistic information on the vocabulary words but help them to understand what they read and apply these words in context. This study focuses on three main objectives; firstly, the challenges facing the computerized Arabic language processing, secondly, the linguistic features to be incorporated in developing the lingual electronic dictionary, and thirdly, the development of this software using instructional development model ADDIE which includes procedures carried out through the design and development of the program such as, choosing the database, selecting the lexical, linguistic, and morphological content, outlining the selected software developmental tools used, ensuring its effectiveness through the actual testing, presenting the results, and selecting the method used in analysing them statistically. The methods used in the study are in three folds; using inductive approach for reviewing the literature, applying computer linguistic analysis approach during analysing the language data for the software, and development approach through the implementation of ADDIE model. The study output is resulting from the successful development of the lingual electronic dictionary program incorporated with the designated linguistic features. In conclusion, the authors summarized some important points in the field of developing the Arabic electronic dictionary with the hope that this study shades some lights in the design and development of the similar software and for the similar purposes in future.